THE DIFFERENCES BETWEEN INDIVIDUAL-TYPOLOGICAL PECULIARITIES OF BELIEVERS IN RELATIONSHIP WITH THE TYPE OF THEIR RELIGIOUS ORIENTATION - P. Politova, Svetlana; V. Silaeva , Zoya; R. Bikusheva, Alina (Gênero & Direito, 2019)
The paper is devoted to the problems of the psychology of believers, which are relevant to modern science. The paper analyses the results of a study on the relationship between the characteristics of a person’s religiosity and his/her individual typological characteristics. To conduct the study, a theoretical analysis was used, as well as reliable and valid methods of psychological diagnosis were applied: a scale of religious orientation by G. Allport and D. Ross, an individually typological questionnaire by L.N. Sobchik, test “Study of the subjective control level” (SCL); processing of the results was carried out using mathematical statistics methods, including t-student test and correlation analysis. The study found differences in the level of subjective personality control between believers with an external and internal religious orientation, namely that people with an external religious orientation are more extroverts than introverts. It was also found that external religiosity is inversely related to most indicators of the locus of control. The results of the study are important to expand understanding of the psychology of believers. An important conclusion that the study allows us to draw is the fact that the selection of believers by their individual typological characteristics is not uniform, which means that research on the psychology of believers should be carried out in the context of their religious orientation.